Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1088/1748-3190/acca59
|View full text |Cite
|
Sign up to set email alerts
|

Social competence improves the performance of biomimetic robots leading live fish

Abstract: Collective motion is commonly modeled with static interaction rules between agents. Substantial empirical evidence indicates, however, that animals may adapt their interaction rules depending on a variety of factors and social contexts. Here, we hypothesized that leadership performance is linked to the leader's responsiveness to the follower's actions and we predicted that a leader is followed longer if it adapts to the follower's avoidance movements. We tested this prediction with live guppies that interacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Live fish did not follow a virtual fish as much if it only swam into the center (Stowers et al, 2017). Experiments using guppies and a biomimetic robot suggest a similar mechanism: social responsiveness of the robot led to less avoidance of the robot (Maxeiner et al, 2023). Together, these studies suggest that fish do not blithely follow other fish, but that their willingness to follow depends on the willingness of the other fish to follow them.…”
Section: Social Behaviorsmentioning
confidence: 91%
“…Live fish did not follow a virtual fish as much if it only swam into the center (Stowers et al, 2017). Experiments using guppies and a biomimetic robot suggest a similar mechanism: social responsiveness of the robot led to less avoidance of the robot (Maxeiner et al, 2023). Together, these studies suggest that fish do not blithely follow other fish, but that their willingness to follow depends on the willingness of the other fish to follow them.…”
Section: Social Behaviorsmentioning
confidence: 91%
“…In the experiments described in the article by Maxeiner et al [11], authors used a robotic fish replica (programmed as a socially competent leader) to interact with individual female guppies (Poecilia reticulata Peters) and to investigate how they adapt their rules based on social contexts. The guppies followed the socially competent robot longer when it adapted to their avoidance movements.…”
Section: Microscopic Viewmentioning
confidence: 99%
“…Aside from using particle models and observation studies, robotic fish embedded within a school of fish are being used to observe and influence the behaviors of fish [44,45]. Researchers have demonstrated that the appearance and locomotion of a robot play crucial roles in its successful assimilation within a school of biological fish [46,47].…”
Section: Fish Behaviorsmentioning
confidence: 99%